Carta do Cônsul em Cantão para o Bispo de Macau, relativamente os relações entre franceses e portugueses em Hainan (1891)
This official ecclesiastical dispatch, dated 1 June 1891, from António, Bishop of Macau, to the Portuguese Chargé d'Affaires in China, forms part of a formal correspondence initiated in response to inquiries regarding missionary activities and Christian communities in southern China during the mid-to-late nineteenth century. The document, certified by both the General Secretariat of the Government of Macau and the Portuguese Consulate in Canton, provides retrospective information on three key incidents involving Catholic missions under the Diocese of Macau. It references the Jiang-tê incident of 1853–1854, detailing French consular intervention with the Canton Viceroy to resolve damages against Christians, though the source of the $200 compensation remains unclear. The text also outlines the acquisition of land at Hoi-haw for the Hainan mission through Joseph James Poynter, registered at the British consulate, illustrating external financial support from Macau. Additionally, it reports abuses against Christians in Coloane, Ngao-ca, and Siem-tin-san in February 1884, resolved through diplomatic representation by the French consul to the Tao-tai, resulting in restored peace. The document serves as a primary source on ecclesiastical administration, cross-colonial legal jurisdictions, and Sino-foreign relations in late Qing China, reflecting the interplay between religious missions, local resistance, and consular diplomacy in the South China coastal region.
S16.E24.P11/87273
Keywords: Bishop of Macau; British Consulate registration; Christian communities; Coloane abuses; Colonial Legal Framework; Diocese of Macau; Ecclesiastical Dispatch; External Financial Support; French consul diplomacy; French-Portuguese relations; Government of Macau certification; Hainan mission; Hoi-haw land acquisition; Jiang-tê incident; Joseph James Poynter; Late Qing Dynasty; Local Resistance To Missions; Macau diocese correspondence; Missionary Activities; Ngao-ca; Portuguese Consul in Canton; Religious interplay; Siem-tin-san; Tao-tai representation; Transcription